Association Between Sugar-Sweetened Beverage Consumption and Executive Function Among Chinese Tibetan Adolescents at High Altitude - Zhang, Feng; Yin, Xiaojian; Liu, Yuan; Li, Ming; Gui, Xiaoying; Bi, Cunjian (Frontiers in Nutrition, 2022)
Objective: To estimate the association between sugar-sweetened beverage (SSB) consumption and executive function (EF) among Chinese Tibetan adolescents. Method: Using three stages by stratified cluster sampling, 1427 Chinese Tibetan adolescents were recruited from Tibet, China. SSB consumption status was obtained by questionnaires and the three core EFs (inhibition, working memory, and cognitive flexibility) were tested by a modified Eriksen flanker task, N-back shift and a more-odd shifting task. One-way ANOVA or Chi-square test was used to compare SSB consumption in different categories. Taking the SSB consumption 0 time/week group as the reference, and using three Models, general linear regression (for continuous variable) or Logical regression (classified variable) was conducted to analyze the relationship between SSB consumption and EF for Chinese Tibetan children and adolescents. Result: After adjustment of all the covariant in Model 2, all the executive function index were higher in Chinese Tibetan adolescents with SSB consumption ≥2 time/week than that with SSB consumption 0 time/week (by 21.325ms (95%CI: 6.724, 35.926), 8.206ms(95%CI: 7.063, 9.350), 90.458ms (95%CI: 28.688, 152.227), 147.613ms (95%CI: 81.423, 213.803), 116.175ms (95%CI: 74.477, 157.872), 112.413ms (95%CI: 71.302, 153.524) for incongruent RT, RT difference in incongruent and congruent, 1-back RT, 2-back RT, Heterogeneous RT, RT difference in Heterogeneous and Homogeneous respectively). Conclusions: The results suggested that SSB consumption was associated with poorer executive function in Chinese Tibetan adolescents. SSB consumption should be controlled for healthy brain development of Chinese Tibetan adolescents.